2015
DOI: 10.1016/j.quascirev.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

The origin of grasslands in the temperate forest zone of east-central Europe: long-term legacy of climate and human impact

Abstract: The post-glacial fate of central European grasslands has stimulated palaeoecological debates for a century. Some argued for the continuous survival of open land, while others claimed that closed forest had developed during the Middle Holocene. The reasons behind stability or changes in the proportion of open land are also unclear. We aim to reconstruct regional vegetation openness and test the effects of climate and human impact on vegetation change throughout the Holocene. We present a newly dated pollen reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 89 publications
6
97
0
13
Order By: Relevance
“…Comparisons of HYDE with REVEALS reconstructions that include the heather (HL) fractions do not match as well (slope of 0.828; Figure S2), and we omitted HL from our primary analysis. Though heathlands can develop due to anthropogenic influences such as grazing and fire, many are natural and do not result from human activities [53,54,63]. This evaluation of the REVEALS method provides confidence that the REVEALS reconstructions are suitable for the evaluation of KK10 and HYDE scenarios for preindustrial time.…”
Section: Discussionmentioning
confidence: 86%
“…Comparisons of HYDE with REVEALS reconstructions that include the heather (HL) fractions do not match as well (slope of 0.828; Figure S2), and we omitted HL from our primary analysis. Though heathlands can develop due to anthropogenic influences such as grazing and fire, many are natural and do not result from human activities [53,54,63]. This evaluation of the REVEALS method provides confidence that the REVEALS reconstructions are suitable for the evaluation of KK10 and HYDE scenarios for preindustrial time.…”
Section: Discussionmentioning
confidence: 86%
“…The proportion of cultivated cereals in pollen assemblages of the last hundred years reached 7%, demonstrating the presence of arable lands adjacent to the peatland (Koff and Punning, 2002 Saarse et al, 2010;Bradley et al, 2013;Kunes et al, 2015). In the central part of…”
Section: Discussionmentioning
confidence: 99%
“…Fire, livestock grazing and agriculture have been detected during the late Holocene in a number of studies (Behre 1981;Kalis et al, 2003;Bradley et al, 2013;Kunes et al, 2015) and are suggested to have had a substantial impact on vegetation (Feurdean et al, 2015). These direct human impacts can potentially both demonstrate the human consequences of climate change and complicate interpretation of vegetation change in strictly climatic terms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Magyari et al (2010) identified wooded steppe, which represents a highly suitable habitat for A. vernalis, as the main vegetation type in the Hungarian Plain during the first half of the Holocence. Further, palaeo-environmental data of the Pannonian Plain provided evidence that about 20% of the landscape were characterised by a stable openness during the entire Holocene, and that Neolithic people contributed to maintain these existing open habitats (Kune s et al 2015). The presence of open landscapes in the Middle Ages is also well documented, both in Central Europe (Poschlod & WallisDeVries 2002) and in Russia (Chibilyev 1998).…”
Section: Core-periphery Gradientmentioning
confidence: 99%